Analysis of the Phenomenon of the Transfer of Waqaf Assets in Muslim Societies - Zulkifli, Musa; Syaputra, Andra; Fauzi, M.; Ediz, M. Hidayat; Nuraiman, Nuraiman (Samara: Journal of Islamic Law and Family Studies, 2024)
This research was motivated by discovering waqf land originally built with a prayer room (mushalla). The position of this waqf land is on a hill. However, the prayer room that had been built there was dismantled by the wakif's descendants and moved to another location. The location of the prayer room which was demolished was then used to build a house. This research aims to analyze the transition of the function of waqf land according to Law Number 41 of 2004. This research uses qualitative research methods with a descriptive approach. Data sources include direct interviews, observation, and documentation. The author uses a normative juridical and empirical juridical approach in analyzing the transition of the function of waqf land by Law Number 41 of 2004. Based on the results of this research analysis, the results showed that first, the public's view of the transfer of waqf land shows that some people still do not know the laws governing waqf land. This is proven by the existence of several individuals who have transferred the function of waqf land. Second, the waqf land originally had a prayer room on it and was located on a hill. The prayer room was dismantled by the wakif's grandchildren and reused elsewhere. The location of the prayer room which was demolished was then used by the wakif's grandchildren to build a house. Third, an analysis of Law Number 41 of 2004 concerning the Transfer of Waqf Land shows that the status of waqf land that has been allocated is prohibited from being changed or transferred in any form except for exchange for the public interest by the spatial planning contained in Law Number 41 of 2004 concerning Waqf Articles 1 and 2.